Mycobacterium fortuitum skin infections after subcutaneous injections with Vietnamese traditional medicine: a case report - Lan, N; Kolader, M; Dung, N; Campbell, J; Tham, N; Chau, N; Van Doorn, H; Le, D (BioMed Central, 2014)
Background: Iatrogenic skin and soft tissue infections by rapidly growing mycobacteria are described with increasing frequency, especially among immunocompromised patients. Case presentation: Here, we present an immunocompetent patient with extensive Mycobacterium fortuitum skin and soft tissue infections after subcutaneous injections to relieve joint pains by a Vietnamese traditional medicine practitioner. Moreover, we present dilemmas faced in less resourceful settings, influencing patient management. Conclusion: This case illustrates the pathogenic potential of rapid growing mycobacteria in medical or non-medical skin penetrating procedures, their world-wide distribution and demonstrates the dilemmas faced in settings with fewer resources.